Hypoxia and TNF‐alpha modulate extracellular vesicle release from human induced pluripotent stem cell‐derived cardiomyocytes - Margarida Viola; Maarten P. Bebelman; Renee G. C. Maas; Willemijn S. deVoogt; Frederik J. Verweij; Cor S. Seinen; Saskia C. A. deJager; Pieter Vader; Dirk Michiel Pegtel; Joost Petrus Gerardus Sluijter (Journal of Extracellular Vesicles)
Abstract Extracellular vesicles (EVs) have emerged as important mediators of intercellular communication in the heart under homeostatic and pathological conditions, such as myocardial infarction (MI). However, the basic mechanisms driving cardiomyocyte‐derived EV (CM‐EV) production following stress are poorly understood. In this study, we generated human induced pluripotent stem cell‐derived cardiomyocytes (hiPSC‐CMs) that express NanoLuc‐tetraspanin reporters. These modified hiPSC‐CMs allow for quantification of tetraspanin‐positive CM‐EV secretion from small numbers of cells without the need for time‐consuming EV isolation techniques. We subjected these cells to a panel of small molecules to study their effect on CM‐EV biogenesis and secretion under basal and stress‐associated conditions. We observed that EV biogenesis is context‐dependent in hiPSC‐CMs. Nutrient starvation decreases CM‐EV secretion while hypoxia increases the production of CM‐EVs in a nSmase2‐dependent manner. Moreover, the inflammatory cytokine TNF‐α increased CM‐EV secretion through a process involving NLRP3 inflammasome activation and mTOR signalling. Here, we detailed for the first time the regulatory mechanisms of EV biogenesis in hiPSC‐CMs upon MI‐associated stressors.